Tinjauan Hukum Penyediaan dan Pengelolaan Ruang Terbuka Hijau berdasarkan Prinsip Good Environmental Governance di Kabupaten Karawang - Mella Ismelina Farma Rahayu; Romi Galih Prabowo; Afrizal Hadi Permana; Aldiansyah Yudha Prawira; Raden Achmad Nur Rizki; Muhamad l Haris Zulkarnaen Sitompul (UNES Law Review, 2023)
This research discusses the relationship between green open space (RTH) and good environmental governance (good environmental governance). Good environmental governance is an extension of good government, which refers to the principles of good governance in the context of the environment. The government's role in providing green open space that can be enjoyed by the wider community is closely related to public policy making. This public policy involves a policy-making process that leads to certain goals and involves steps taken by the government. Green open space has various benefits, both ecologically, socio-culturally, and aesthetically. Green open space provides comfort, improves the microclimate, increases oxygen reserves, and serves as a means of recreation, social interaction and regional identity. The existence of green open space is also important in maintaining a balance between the natural environment and the built environment in urban areas. In managing green open space, it is important to apply the concept of good environmental governance by taking into account the sustainability of natural resources. Environmental governance understands environmental management through interactions between the state and its people. Green open space management also involves the process of planning, utilization and control which plays an important role in forming a planned urban spatial layout. This study focuses on Karawang Regency, where there is an imbalance between the amount of green open space with public facilities and private buildings. Even though there is still empty land that can be used as green open space, its utilization has not been optimal. In the Karawang Regency strategic plan, an analysis of land use and green open space needs is carried out based on the area and population. Good green open space management efforts in Karawang Regency can help achieve good environmental governance and improve the quality of the environment and the quality of life of its people.